Trends in Emerging Markets, Globalization, Economic Development, Entrepreneurship and Management Strategies as a Result of Cross-Border Cooperation (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
As globalization advances, trends and societal shifts influence several economic and socioeconomic aspects. As cross-border cooperation has been increasing across various regions, this leads to market changes, both established and emerging, trading methods and management aspects. As a result, it is crucial to study the negative and positive changes on an economic and social level emanating from this phenomenon. The inter-relationship between international environments, transactions, and cooperation projects can transform economic and socioeconomic conditions, leading to more enabling and sustainable cities, societies, and regions. The results from new and stronger business networks and cluster environments created through cooperation projects, strategies, synergies, and transactions are already reshaping the socioeconomic panorama.